43 Discrepant Results in Microbiology: A Tale of Two Patients. (11th January 2018) - Abel, Jacob; Wang, Yaohong; Clark, Brittany; Pearlman, Eugene
Abstract: Objective: We report two patients where micro-organism identification by chemical phenotyping (CP) disagreed with mass spectrometry (MS) results. Both patients were white men (59 and 62 years old), were quadriplegic, and had repeated episodes of respiratory failure thought secondary to aspiration pneumonitis and eventually requiring ventilator support. One of the patients died, and the second remained an inpatient seven and six months post-admission. Methods: Both discrepant specimens were tracheal aspirates. Using Microscan (Beckman-Coulter, La Brea, CA) after standard culture procedures resulted in repeated CP of isolates as Shigella species or "rare biotype" in our facility and a reference lab (RL; AEL, Memphis, TN), whereas they were identified as A baumannii by the State Department of Health lab and RL [AEL] using MS. Isolates were sent to a third RL (Lab Corp, Burlington, NC). CP done using both Microscan (an older model) and Vitek (BioMérieux, Durham, NC) also MS-identified A baumannii . The latter was identified on subsequent tracheal aspirates (x3) and BAL specimens on both patients using Microscan in our facility. Results: Isolates were also sent for investigation by Beckman-Coulter. They concluded that the problem involved maintenance of anaerobic conditions in the glucose fermentation well. The procedure uses a layer of mineral oil, but this can be imperfect; in the presence of a strongly oxidase-positive organism, eg, A baumannii, a false-positive "gold" color may be produced (a true positive is yellow), and sporadically, an incorrect identification results. It is apparently left to the technologist to recognize lack of concordance between CP and parameters such as colonial morphology or specimen source, and change the positive fermentation result to negative. Conclusion: It would appear the correct identification was A baumannii, and that MS results may be preferable to CP for micro-organism identification.